Bolt surface anti-corrosion process

Through advanced surface treatment technology and co-permeation treatment, an alloy layer or compound layer anticorrosion layer is formed, and a multi-layer anticorrosion protective film is formed on it, which solves the problem of insufficient uniformity and adhesion of anticorrosion layer in traditional bolt anticorrosion treatment methods. Improves the corrosion resistance and service life of the bolts.

CN119433425AInactive Publication Date: 2025-02-14NANTONG JINGBO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411621750.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional bolt anti-corrosion treatment methods are difficult to ensure the uniformity and adhesion of the anti-corrosion layer, and are prone to local excessive thickness or thinness, and the anti-corrosion layer is easily scratched, resulting in poor anti-corrosion performance.

Method used

Advanced surface treatment technology is adopted, including removing oil stains on the surface of the workpiece, removing rust, washing with water to remove acid residues, polishing treatment, co-permeation treatment and surface plating treatment, forming an alloy layer or compound layer anti-corrosion layer with excellent corrosion resistance. , and a multi-layer anticorrosion protective film is formed thereon.

Benefits of technology

The bonding force between the anti-corrosion layer and the bolt matrix is ​​improved, the adhesion and durability of the anti-corrosion layer are enhanced, and the uniform anti-corrosion effect on the bolt surface is ensured, and the local excessive or excessive thinness is avoided, which extends the service life of the bolt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433425A_ABST
    Figure CN119433425A_ABST
Patent Text Reader

Abstract

The invention discloses a bolt surface anti-corrosion process, and relates to the technical field of heat treatment processes, the process comprises the following steps: S1, pretreating a bolt workpiece; s2, polishing treatment is conducted, specifically, the bolt workpiece is mixed with rubber balls and silicon carbide particles and then put into a stirrer to be stirred; and S3, co-permeation treatment is conducted, specifically, a permeation agent is prepared, the polished bolt is put into a co-permeation furnace, the permeation agent, an anti-binding agent and an accelerated diffusion agent are evenly stirred and then put into a diffusion tank, and after a sealing cover of the co-permeation furnace is sealed, alloy elements are permeated into the surface of the bolt through a co-permeation heat treatment technology. The bolt surface is pretreated through advanced surface treatment technologies such as workpiece surface greasy dirt removal, rust removal through acid pickling and acid liquid residue removal through water washing, impurities such as greasy dirt and rust on the bolt surface are removed, the cleanliness and roughness of the bolt surface are improved, and therefore the binding force of an anti-corrosion layer and a bolt base body is enhanced, and the service life of the bolt is prolonged. The problem that an anti-corrosion layer is prone to falling off due to untight combination is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat treatment processes, and in particular to a bolt surface anti-corrosion process. Background Art

[0002] Bolts are common fasteners and are widely used in various machines and structures. However, during use, especially in harsh environments, bolts are susceptible to corrosion, which can lead to reduced strength, loose connections, or even breakage, thus affecting the stability and safety of the entire structure. Therefore, a bolt surface anti-corrosion process has emerged. Bolts treated with this anti-corrosion process have better corrosion resistance and a long service life, thereby ensuring the stable operation of mechanical equipment.

[0003] The existing technology has the following problems: Traditional anti-corrosion treatment methods, such as painting and electroplating, sometimes result in the problem of loose bonding between the anti-corrosion layer and the bolt matrix, which causes the anti-corrosion layer to easily fall off or break, thereby losing the anti-corrosion effect. In the threaded part of the bolt, due to the complex shape, traditional anti-corrosion treatment methods are difficult to ensure the uniformity of the anti-corrosion layer, and it is easy for the anti-corrosion layer to be too thick or too thin in some areas. In addition, the anti-corrosion layer is easily scratched, which affects its anti-corrosion performance. Bolts treated by traditional anti-corrosion treatment methods have a single anti-corrosion performance and are prone to failure. Summary of the invention

[0004] The present invention provides a bolt surface anti-corrosion process to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: A bolt surface anti-corrosion process, the process comprising: S1. Bolt workpiece pretreatment; S2. Polishing treatment: Mix the bolt workpiece with rubber balls and silicon carbide particles and put them into a mixer for stirring; S3, co-penetration treatment: prepare the penetrant, put the polished bolts into the co-penetration furnace, mix the penetrant, anti-adhesive agent and accelerating diffusion agent evenly and put them into the diffusion tank, seal the sealing cover of the co-penetration furnace, and use the co-penetration heat treatment process to infiltrate the alloy elements into the bolt surface, and test the thickness, hardness and corrosion resistance of the alloy co-penetration layer; S4. Surface coating treatment: Use magnetron sputtering or ion implantation technology to coat a layer of Cr protective film on the bolt surface; S5. Inspection and post-maintenance: Carry out quality inspection on the treated bolts, and conduct regular inspection and maintenance to promptly detect and treat surface rusted areas.

[0006] Preferably, the S1 comprises: S11. Remove oil stains from the workpiece surface: Add organic solvent to the heating furnace, then put the bolt workpiece in, and keep it at 320-400℃ for 45-60min until the workpiece surface is oil-free; S12, pickling to remove rust: the degreased bolt workpiece is completely immersed in an acid solution with a mass concentration of 6-12wt%, ultrasonically cleaned at a temperature of 32°C for 15-30min, and the acid solution on the surface of the workpiece is cleaned with purified water; S13. Wash with water to remove acid residue: completely immerse the bolt workpiece after ultrasonic cleaning with acid solution in a sodium bicarbonate solution with a mass concentration of 3-5wt%, and ultrasonically clean it at a temperature of 25°C for 10-15 minutes. After taking out the workpiece, rinse it with purified water for 4-6 minutes.

[0007] Preferably, the acid solution with a mass concentration of 6-12wt% is prepared by mixing a hydrochloric acid solution with a mass concentration of 5-10wt% and a nitric acid solution with a mass concentration of 8-15wt% in a ratio of 1:1, and the organic solvent includes but is not limited to gasoline, kerosene or alcohol.

[0008] Preferably, the diameter of the rubber ball is 0.5-1.5 cm, and the diameter of the silicon carbide particles is 0.05-0.5 cm.

[0009] Preferably, the co-infiltration heat treatment process is specifically to evacuate the sealed diffusion tank to a vacuum degree of 0.001-0.005Pa, bury the bolt workpiece in the zincizing agent, control the furnace filling volume to 60%-85%, the furnace speed to 2-6r / min, the zincizing temperature to 420°C, and when the vacuum pressure gauge shows a positive pressure, open the vent valves at both ends of the co-infiltration furnace for the first venting, close the vent valve after the venting is completed, continue to heat and heat to the furnace temperature of 335°C, and when the vacuum pressure gauge shows a positive pressure, open the vent valves at both ends of the co-infiltration furnace for the second venting, and vent. After the gas is completed, close the vent valve, continue heating to the furnace temperature of 362℃, open the vent valves at both ends of the co-infiltration furnace for the third venting, close the vent valve after the venting is completed, maintain the temperature in the co-infiltration furnace at 225-375℃ for 0.5-3h, and carry out rotary cooling. Stop rotation when the co-infiltration furnace temperature is below 85℃, and take out of the furnace after venting and cooling. The amount of penetrant is 20-50kg per ton of steel parts, the amount of anti-adhesive agent is 10%-20% of the volume of the diffusion tank, and the amount of accelerating diffusion agent is 80g-150g per ton of steel parts.

[0010] Preferably, the penetrant is a mixture of nano zinc powder, nano nickel powder, nano rare earth oxide, nano molybdenum iron powder, nano titanium powder, hydrogen peroxide, a dispersant, and a surfactant, wherein the dispersant is nano silicon dioxide, and the surfactant is fatty acid diethanolamine.

[0011] Preferably, the surface coating treatment further comprises: coating a layer of epoxy resin or polyurethane coating on the Cr protective film, or using a polymer composite material to form a protective film, and then performing a curing treatment, wherein the Cr protective film is formed by alternatingly stacking Cr layers and Cr (N) layers.

[0012] Preferably, the quality inspection includes but is not limited to appearance inspection, thickness measurement, and adhesion test.

[0013] Preferably, the bolts are stored in a dry, well-ventilated environment and protected with anti-rust paper, anti-rust oil or anti-rust agent. The bolts may also be sealed and packaged in plastic bags or aluminum foil bags.

[0014] Due to the adoption of the above technical solution, the present invention has the following technical advances compared with the prior art: The present invention provides a bolt surface anti-corrosion process, which pre-treats the bolt surface through advanced surface treatment technologies such as removing oil stains on the workpiece surface, removing rust by pickling, and removing acid residue by water washing, thereby removing oil stains, rust and other impurities on the bolt surface, improving the cleanliness and roughness of the bolt surface, thereby enhancing the bonding force between the anti-corrosion layer and the bolt matrix, solving the problem of easy falling off of the anti-corrosion layer due to loose bonding, further removing tiny flaws on the bolt surface through polishing treatment, improving the surface smoothness and adhesion of the anti-corrosion layer, thereby improving the adhesion and durability of the anti-corrosion layer, and enhancing the anti-corrosion effect of the bolt.

[0015] The present invention provides a bolt surface anti-corrosion process. By using a co-penetration treatment technology, alloy elements are infiltrated into the surface of a bolt workpiece to form an alloy layer or a compound layer anti-corrosion layer with excellent corrosion resistance, thereby ensuring that the anti-corrosion layer can evenly cover the entire bolt surface to avoid the situation where the bolt workpiece is locally too thick or too thin. The size of the bolt workpiece does not change, the formed anti-corrosion layer is not easily scratched, and the anti-corrosion effect is good. The processing parameters such as the processing temperature, time, and concentration in the entire anti-corrosion process are accurately controlled to ensure that the thickness and uniformity of the anti-corrosion layer meet the design requirements, thereby improving the quality stability and uniformity of the anti-corrosion layer.

[0016] The present invention provides a bolt surface anti-corrosion process, which utilizes magnetron sputtering or ion implantation technology to plate a Cr protective film on the bolt surface, and the protective film is formed by alternately stacking Cr layers and Cr (N) layers, thereby improving the anti-corrosion effect of the bolt. In addition, a layer of epoxy resin or polyurethane coating is coated on the Cr protective film, or a polymer composite material is used to form a protective film, thereby achieving a multi-layer anti-corrosion protection effect, effectively alleviating the corrosion of the bolt, reducing later maintenance, and solving the problem that the bolt is easily ineffective due to single anti-corrosion.

[0017] The present invention provides a bolt surface anti-corrosion process. By regularly inspecting and maintaining the bolts, surface rusted parts can be discovered and treated in time, ensuring that the anti-corrosion performance is always kept in a good state, thereby achieving a long-term protective effect. The bolts are sealed and packaged in plastic bags or aluminum foil bags to isolate air and moisture. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a flow chart of the bolt surface anticorrosion process of the present invention; Figure 2 The flowchart of the bolt workpiece pretreatment of the present invention. DETAILED DESCRIPTION

[0019] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0020] like Figure 1 As shown, a bolt surface anti-corrosion process, the process includes: S1. Bolt workpiece pretreatment; S2. Polishing treatment: Mix the bolt workpiece with rubber balls and silicon carbide particles and put them into a mixer for stirring; S3, co-penetration treatment: prepare the penetrant, put the polished bolts into the co-penetration furnace, mix the penetrant, anti-adhesive agent and accelerating diffusion agent evenly and put them into the diffusion tank, seal the sealing cover of the co-penetration furnace, and use the co-penetration heat treatment process to infiltrate the alloy elements into the bolt surface, and test the thickness, hardness and corrosion resistance of the alloy co-penetration layer; S4. Surface coating treatment: Use magnetron sputtering or ion implantation technology to coat a layer of Cr protective film on the bolt surface; S5. Inspection and post-maintenance: Carry out quality inspection on the treated bolts, and conduct regular inspection and maintenance to promptly detect and treat surface rusted areas.

[0021] By introducing advanced surface treatment technology to pre-treat the bolt surface, remove impurities such as oil and rust on the bolt surface, improve the cleanliness and roughness of the bolt surface, thereby enhancing the bonding force between the anti-corrosion layer and the bolt matrix, solving the problem of easy falling off of the anti-corrosion layer due to loose bonding, and enhancing the anti-corrosion effect of the bolt. Through polishing treatment, further remove the tiny flaws on the bolt surface, improve the surface finish and adhesion of the anti-corrosion layer. Through a specific co-infiltration heat treatment process, the alloy elements are infiltrated into the surface of the bolt workpiece to form an alloy layer or compound layer anti-corrosion layer with excellent corrosion resistance, ensuring that the anti-corrosion layer can evenly cover the entire bolt surface to avoid local over-thickness or over-thinness. In this process, the size of the bolt workpiece does not change, the formed anti-corrosion layer is not easy to be scratched, and the anti-corrosion effect is good. The use of advanced surface treatment technology, magnetron sputtering or ion implantation technology, etc., can improve the high adhesion and durability of the anti-corrosion layer. Regular inspection and maintenance of the bolts can timely detect and deal with surface rust, ensure that its anti-corrosion performance is always maintained in good condition, and achieve long-term protection.

[0022] like Figure 2 As shown, S1 includes: S11. Remove oil stains from the workpiece surface: Add organic solvent to the heating furnace, then put the bolt workpiece in, and keep it at 320-400℃ for 45-60min until the workpiece surface is oil-free, which can completely remove the oil stains from the workpiece surface; S12. Pickling to remove rust: completely immerse the degreased bolt workpiece in an acid solution with a mass concentration of 6-12wt%, perform ultrasonic cleaning at a temperature of 32°C for 15-30 minutes, and use purified water to remove the acid solution on the surface of the workpiece, and completely remove rust or oxide layer and other pollutants on the bolt surface; S13, water washing to remove acid residue: the bolt workpiece after ultrasonic cleaning with acid solution is completely immersed in a sodium bicarbonate solution with a mass concentration of 3-5wt%, and ultrasonically cleaned at a temperature of 25°C for 10-15min. After taking out the workpiece, rinse it with purified water for 4-6min. This step can neutralize the acidic substances on the surface of the bolt and prepare for the subsequent polishing process.

[0023] By introducing advanced surface treatment technologies, such as removing oil stains on the workpiece surface, pickling to remove rust, and water washing to remove acid residues, oil stains, rust and other impurities on the bolt surface are removed, the cleanliness and roughness of the bolt surface are improved, thereby enhancing the bonding strength between the anti-corrosion layer and the bolt matrix.

[0024] The acid solution with a mass concentration of 6-12wt% is prepared by mixing a hydrochloric acid solution with a mass concentration of 5-10wt% and a nitric acid solution with a mass concentration of 8-15wt% in a ratio of 1:1, and the organic solvent includes but is not limited to gasoline, kerosene or alcohol.

[0025] The diameter of the rubber ball is 0.5-1.5 cm, and the diameter of the silicon carbide particle is 0.05-0.5 cm.

[0026] The specific process of co-infiltration heat treatment is to evacuate the sealed diffusion tank to a vacuum degree of 0.001-0.005Pa, bury the bolt workpiece in the zincizing agent, control the furnace filling volume to 60%-85%, the furnace speed to 2-6r / min, and the zincizing temperature to 420℃. When the vacuum pressure gauge shows positive pressure, open the vent valves at both ends of the co-infiltration furnace for the first venting. After the venting is completed, close the vent valves and continue to heat and heat to the furnace temperature of 335℃. When the vacuum pressure gauge shows positive pressure, open the vent valves at both ends of the co-infiltration furnace for the second venting. After the venting is completed, Then close the vent valve, continue heating to the furnace temperature of 362℃, open the vent valves at both ends of the co-infiltration furnace for the third venting, close the vent valve after venting, maintain the temperature in the co-infiltration furnace at 225-375℃ for 0.5-3h, and carry out rotary cooling. Stop rotation when the co-infiltration furnace temperature is below 85℃, and take out of the furnace after venting and cooling. The amount of penetrant is 20-50kg per ton of steel parts, the amount of anti-adhesive is 10%-20% of the volume of the diffusion tank, and the amount of accelerating diffusion agent is 80g-150g per ton of steel parts.

[0027] The penetrant is prepared by mixing nano zinc powder, nano nickel powder, nano rare earth oxide, nano molybdenum iron powder, nano titanium powder, hydrogen peroxide, a dispersant and a surfactant. The dispersant is nano silicon dioxide and the surfactant is fatty acid diethanolamine.

[0028] The surface coating treatment also includes: coating a layer of epoxy resin or polyurethane coating on the Cr protective film, or using a polymer composite material to form a protective film, and then performing a curing treatment. The Cr protective film is formed by alternating Cr layers and Cr (N) layers.

[0029] A layer of Cr protective film is plated on the surface of the bolt, and the protective film is composed of alternating Cr layers and Cr (N) layers, which can further improve the anti-corrosion effect of the bolt. A layer of epoxy resin or polyurethane coating is coated on the Cr protective film, or a polymer composite material is used to form a protective film to achieve a multi-layer anti-corrosion protection effect, effectively alleviate the corrosion of the bolt, reduce subsequent maintenance, and solve the problem that the bolt is prone to failure due to single anti-corrosion.

[0030] Quality inspection includes but is not limited to appearance inspection, thickness measurement, and adhesion testing.

[0031] Store the bolts in a dry, well-ventilated environment and protect them with anti-rust paper, anti-rust oil or anti-rust agent to avoid contact with moisture and corrosive media to prevent oxidation corrosion. You can also use plastic bags or aluminum foil bags to seal the bolts to isolate them from air and moisture.

[0032] In summary, an organic solvent is added to the heating furnace, and then the bolt workpiece is placed in it and kept warm at 400°C for 60 minutes until the surface of the workpiece is oil-free, and the oil stains on the surface of the workpiece can be completely removed. The deoiled bolt workpiece is completely immersed in an acidic solution with a mass concentration of 12wt%, and ultrasonically cleaned at 32°C for 30 minutes. The acidic solution on the surface of the workpiece is cleaned with purified water to completely remove pollutants such as rust or oxide layer on the surface of the bolt. The bolt workpiece after ultrasonic cleaning with the acidic solution is completely immersed in a sodium bicarbonate solution with a mass concentration of 5wt%, and ultrasonically cleaned at 25°C for 15 minutes. After taking out the workpiece, it is rinsed with purified water for 6 minutes. This step can neutralize the acid on the surface of the bolt. The advanced surface treatment technology is introduced to remove oil, rust and other impurities on the bolt surface, improve the cleanliness and roughness of the bolt surface, and enhance the bonding force between the anti-corrosion layer and the bolt matrix. The pretreated bolt workpiece is mixed with rubber balls and silicon carbide particles and then put into a mixer for stirring for 60 minutes to further remove tiny flaws on the bolt surface, improve the surface finish and adhesion of the anti-corrosion layer. The penetrant is prepared, and the polished bolt is loaded into the co-penetration furnace. The penetrant, anti-adhesive agent and accelerated diffusion agent are stirred evenly and loaded into the diffusion tank. After the sealing cover of the co-penetration furnace is sealed, the alloy elements are infiltrated into the bolt surface through the co-penetration heat treatment process to form an alloy layer or compound layer anti-corrosion layer with excellent corrosion resistance, ensuring that the anti-corrosion layer can The entire bolt surface is evenly covered to avoid local over-thickness or over-thinness. The size of the bolt workpiece does not change during the co-penetration treatment process. The formed anti-corrosion layer is not easy to be scratched and has a good anti-corrosion effect. The thickness, hardness and corrosion resistance of the alloy co-penetration layer are tested. A layer of Cr protective film is plated on the surface of the qualified bolts using magnetron sputtering or ion implantation technology. The protective film is composed of alternating Cr layers and Cr (N) layers, which can improve the anti-corrosion effect of the bolts. In addition, a layer of epoxy resin or polyurethane coating is coated on the Cr protective film, or a polymer composite material is used to form a protective film to achieve a multi-layer anti-corrosion protection effect, effectively alleviate the corrosion of the bolts, and reduce subsequent maintenance. The appearance of the treated bolts is inspected. Inspection, thickness measurement, adhesion test and other quality inspections, store the bolts in a dry and well-ventilated environment, and use anti-rust paper, anti-rust oil or rust inhibitor for protection, avoid contact between the bolts and moisture, corrosive media, etc., to prevent oxidative corrosion, and use plastic bags or aluminum foil bags to seal the bolts for packaging, which can isolate air and moisture. Regular inspection and maintenance of the bolts can promptly detect and deal with surface rust, ensure that their anti-corrosion performance is always maintained in good condition, and achieve long-term protection. By accurately controlling the processing temperature, time, concentration and other parameters during the entire anti-corrosion process, ensure that the thickness and uniformity of the anti-corrosion layer meet the design requirements, and improve the quality stability and uniformity of the anti-corrosion layer.

[0033] The above generally describes the present invention in detail, but it is obvious to a person skilled in the art that some modifications or improvements can be made to the present invention. Therefore, modifications or improvements that do not depart from the spirit of the present invention are within the scope of protection of the present invention.

Claims

1. A bolt surface anti-corrosion process, characterized in that: The process includes: S1. Bolt workpiece pretreatment; S2. Polishing treatment: Mix the bolt workpiece with rubber balls and silicon carbide particles and put them into a mixer for stirring; S3, co-penetration treatment: prepare the penetrant, put the polished bolts into the co-penetration furnace, mix the penetrant, anti-adhesive agent and accelerating diffusion agent evenly and put them into the diffusion tank, seal the sealing cover of the co-penetration furnace, and use the co-penetration heat treatment process to infiltrate the alloy elements into the bolt surface, and test the thickness, hardness and corrosion resistance of the alloy co-penetration layer; S4. Surface coating treatment: Use magnetron sputtering or ion implantation technology to coat a layer of Cr protective film on the bolt surface; S5. Inspection and post-maintenance: Carry out quality inspection on the treated bolts, and conduct regular inspection and maintenance to promptly detect and treat surface rusted areas.

2. A bolt surface anticorrosion process according to claim 1, characterized in that: The S1 includes: S11. Remove oil stains from the workpiece surface: Add organic solvent to the heating furnace, then put the bolt workpiece in, and keep it at 320-400℃ for 45-60min until the workpiece surface is oil-free; S12, pickling to remove rust: the degreased bolt workpiece is completely immersed in an acid solution with a mass concentration of 6-12wt%, ultrasonically cleaned at a temperature of 32°C for 15-30min, and the acid solution on the surface of the workpiece is cleaned with purified water; S13. Wash with water to remove acid residue: completely immerse the bolt workpiece after ultrasonic cleaning with acid solution in a sodium bicarbonate solution with a mass concentration of 3-5wt%, and ultrasonically clean it at a temperature of 25°C for 10-15 minutes. After taking out the workpiece, rinse it with purified water for 4-6 minutes.

3. A bolt surface anticorrosion process according to claim 2, characterized in that: The acid solution with a mass concentration of 6-12wt% is prepared by mixing a hydrochloric acid solution with a mass concentration of 5-10wt% and a nitric acid solution with a mass concentration of 8-15wt% in a ratio of 1:1, and the organic solvent includes but is not limited to gasoline, kerosene or alcohol.

4. The bolt surface anticorrosion process according to claim 1, characterized in that: The diameter of the rubber ball is 0.5-1.5 cm, and the diameter of the silicon carbide particles is 0.05-0.5 cm.

5. The bolt surface anticorrosion process according to claim 1, characterized in that: The co-infiltration heat treatment process specifically comprises the following steps: evacuating the sealed diffusion tank to a vacuum degree of 0.001-0.005 Pa, burying the bolt workpiece in the zincizing agent, controlling the furnace filling volume to 60%-85%, the furnace speed to 2-6r / min, and the zincizing temperature to 420°C. When the vacuum pressure gauge shows a positive pressure, the vent valves at both ends of the co-infiltration furnace are opened for the first venting. After the venting is completed, the vent valves are closed, and the heating is continued to be raised to a furnace temperature of 335°C. When the vacuum pressure gauge shows a positive pressure, the vent valves at both ends of the co-infiltration furnace are opened for the second venting. After the venting is completed, After completion, close the vent valve, continue heating to the furnace temperature of 362℃, open the vent valves at both ends of the co-infiltration furnace for the third venting, close the vent valve after venting, maintain the temperature in the co-infiltration furnace at 225-375℃ for 0.5-3h, and rotate to cool down. Stop rotation when the co-infiltration furnace temperature is below 85℃, vent and cool down, and take out of the furnace. The amount of penetrant is 20-50kg per ton of steel parts, the amount of anti-adhesive is 10%-20% of the volume of the diffusion tank, and the amount of accelerating diffusion agent is 80g-150g per ton of steel parts.

6. A bolt surface anticorrosion process according to claim 5, characterized in that: The penetrant is prepared by mixing nano zinc powder, nano nickel powder, nano rare earth oxide, nano molybdenum iron powder, nano titanium powder, hydrogen peroxide, a dispersant and a surfactant. The dispersant is nano silicon dioxide and the surfactant is fatty acid diethanolamine.

7. The bolt surface anticorrosion process according to claim 1, characterized in that: The surface coating treatment also includes: coating a layer of epoxy resin or polyurethane coating on the Cr protective film, or using a polymer composite material to form a protective film, and then performing a curing treatment. The Cr protective film is formed by alternating Cr layers and Cr (N) layers.

8. The bolt surface anticorrosion process according to claim 1, characterized in that: The quality inspection includes but is not limited to appearance inspection, thickness measurement, and adhesion test.

9. The bolt surface anticorrosion process according to claim 1, characterized in that: Store the bolts in a dry, well-ventilated environment and protect them with anti-rust paper, anti-rust oil or anti-rust agent. You can also use plastic bags or aluminum foil bags to seal the bolts.